A companion to cultural memory studies - Erll, Astrid; Nünning, Ansgar (De Gruyter, 2010)
This companion represents the interdisciplinary and international field of ""cultural memory studies"" in one volume. Articles by renowned international scholars offer readers a unique overview of the key concepts of cultural memory studies. The book not only documents current research in an unprecedented way; it also serves as a forum for bringing together approaches from areas as varied as sociology, political sciences, history, theology, literary studies, media studies, philosophy, psychology, and neurosciences.""Cultural memory studies"" - as defined in this book - came into being at the beginning of the 20th century, with the works of Maurice Halbwachs on mèmoire collective. In the course of the last two decades this area of research has witnessed a veritable boom in various countries and disciplines. As a consequence, the study of the relation of ""culture"" and ""memory"" has diversified into a wide range of approaches. This companion is based on a broad understanding of ""cultural memory"" as the interplay of present and past in sociocultural contexts. It presents concepts for the study of individual remembering in a social context, group and family memory, national memory, the various media of memory, and finally the host of emerging transnational lieux de mèmoire such as 9/11. This book first appeared as a hardback volume in the De Gruyter series ""Media and Cultural Memory"" under the title ""Cultural Memory Studies: An International and Interdisciplinary Handbook"". With the present companion the original articles are reissued in an affordable paperback edition.